A Systematic Approach to the Development of Basic Models of the Behavior of Business Entities and its Harmonization - Mykytenko, V.; Chuprina, M.; Serhiienko, S. (Економічний вісник Донбасу, 2022)
The authors have formed and substantiated the basic models of behavior of a plurality of business entities, presented in the form of combined conceptual and analytical model solutions, taking into account both a clear sequence of implementation of organizational, economic and institutional procedures, and economic and psychological factors of choosing which one to use in business practice. Proposed: a) a model of monetary-entrepreneurial (innovative) behavior - it is described by the content of the determining factors for generating monetary signs of the real behavior of business entities, the key factors for generating social adaptability in modern monetary culture and the significance of these factors, factor load factors; b) a model of marketing and investment behavior, detailed according to a binary set of principles for implementing new models of investment and marketing behavior; c) model of adaptive-cavernous cognitive behavior - identified by the triad of principles of adaptive, cavernous and cognitive behavior. A closed scheme of formalization, in five stages, has been developed for choosing one of the three combined basic models of behavior of business entities, which is carried out in phases: identification of prerequisites for choice in a certain space and time; description of initial model solutions and determination of objective functions; implementation of a closed loop for choosing a basic behavior model. Авторами сформовано та обґрунтовано базові моделі поведінки множини суб'єктів господарської діяльності, репрезентованих у вигляді комбінованих концептуально-аналітичних модельних вирішень із урахуванням як чіткої послідовності реалізації організаційно-економічних та інституційних процедур, так і економіко-психологічних факторів вибору котрої з них для використання у практиці господарювання. Запропоновано: а) модель монетарно-підприємницької (інноваційної) поведінки – її описано за змістовністю визначальних факторів генерування монетарних ознак реальної поведінки суб’єктів господарювання, ключовими факторами генерування соціальної адаптивності в сучасній монетарній культурі та вагомістю цих факторів, факторних чинників навантаження; б) модель маркетингово-інвестиційної поведінки, яку деталізовано за бінарним комплексом принципів реалізації нових моделей інвестиційної та маркетингової поведінки; в) модель адаптивно-каверної когнітивної поведінки – ідентифіковано за тріадою принципів адаптивної, каверної і когнітивної поведінки. Розроблено замкнену схему формалізації, за п’ятьма етапами, вибору однієї з трьох комбінованих базових моделей поведінки суб'єктів господарювання, що виконується за фазами: ідентифікація передумов вибору у певному просторі та часі; опис вихідних модельних рішень та визначення цільових функцій; реалізація замкненого циклу вибору базової моделі поведінки.